Analisis Kompetensi Guru Pendidikan Anak Usia Dini dalam Pelaksanaan Pembelajaran dI TK Tunas Bangsa Kolaka Timur - Ifa Rahmiati Azahra; Rasmi Rasmi (Diniyah: Jurnal Pendidikan Dasar, 2021)
The purpose of this article is to examine the pedagogic competence of early childhood education teachers who hold PAUD undergraduate and non-PAUD undergraduate educational qualifications. This research employed descriptive qualitative research. Data were collected through interviews, observation and documentation. Data analysis was in the form of data reduction techniques, data presentation and drawing conclusion. Testing the validity of the data was done by triangulation of sources, techniques and time. The results showed that teachers with PAUD undergraduate qualifications seemed to have an adequate understanding of the character and development of students which was implied in the selection of materials, media, and teaching materials which were then adjusted to the level of child development. On the other hand, teachers with non-graduate PAUD qualifications do not seem to understand well the mastery of the material, the making of lesson plans, and the evaluation of learning. To improve the quality of teachers, several implemented policies in TK Tunas Bangsa are encouring the teachers to continue to higher level of education, attend training related to the curriculum, and increase skills in operating computers.Keywords: Pedagogics Competence, PAUD Teachers